Islam in Japan in a Contemporary Paradigm - Ogi, Aleksandra-Megumi (Этническая культура, 2025)
The article examines the development of Islam in Japan from Noda Masataro – the first Japanese to convert to Islam in 1891 in the Ottoman Empire, to the present day. Particular attention is paid to the coverage of Japan’s Islamic policy in 1930–1945, and how Islam is understood by the Japanese through the prism of Shintoism and Buddhism. There is currently a growing number of Japanese Muslims. It is noteworthy that most of them are women married to Muslims, but the Japanese themselves, mostly young intellectuals, are beginning to embrace Islam. There are also second-generation Muslims in Japan, those who have one or both parents who are Muslim. One of the parents may be a foreigner. In this case, such people face problems of identity and the ability to integrate into traditional Japanese society. One of the main problems of Japanese Muslims is the problem of burial according to the Muslim tradition, since in Japan, cremation is mostly chosen in such cases. In general, Japanese citizens are religiously tolerant and measures have been taken by the authorities to maintain such sentiments and this despite the growing Islamophobic sentiments in Europe and America, which may sow fear among the Japanese against Muslims.